The market of battery electric vehicles in Portugal and Mobiletric´s Pro-Station price analysis - Coelho, Maria Leonor Nunes Pinto (2019)
The goal of this dissertation is to make a Market Analysis for Battery Electric Vehicles (BEV) in Portugal as well as analyse the variables which affect the price consumers are willing to pay for Mobiletric’s Pro-Station. Throughout external research, interviews, and surveys I was able to acknowledge that the market of BEVs is considerably growing and by 2025 it will represent 2.7% and 15% of the number of total cars and sales in Portugal (as opposed to the current 0.4% and 0.2% in 2019). Nowadays, the number of charging poles is insufficient to fulfil all the demand, and that is the most significant disadvantage to BEV’s users. Despite the reduced utilization costs of such cars, the purchase price is another main barrier. Nonetheless, as the economy of scales of car producers and technology evolves, the price will decrease. BEV’s users prefer to charge their cars at home and in standard chargers, which are not paid and protect the car’s battery. However, as the deployment of BEVs increases, lower income people with no garage at home will start to purchase such vehicles and they will have no option but to rely on the public charging infrastructures. On the other hand, public charging poles are being auctioned to private companies which will ensure a more reliable and wider charging network. Lastly, the price consumers are willing to pay for Mobiletric’s Pro-Station (a private charging venue) seems to depend significantly on the kilometres made per day by each person.